HUBUNGAN ANTARA TEORI PERKEMBANGAN KOGNITIF PIAGET DAN TEORI BELAJAR BRUNER - S. Thoriqul Huda; Endro Tri Susdarwono (Jurnal Muassis Pendidikan Dasar, 2023)
This study intends to provide a description related to the correlation of Jean Piaget's cognitive development theory to Jerome S. Bruner's learning theory in learning related to the process of rainbow occurrence. The correlated relationships include the pre operational stage of Piaget's theory to the iconic stage of Bruner's theory, and the relationship of Piaget's concrete operational stage to the symbolic stage of Bruner's theory. The quantitative research design used was the pre-experimental design, with the form of the pre-experimental design used being the one-shot case study design. This method is intended to find the relationship of certain variables to other variables. The sampling technique used for this research design is purposive sampling. The samples taken were students aged 3-7 years and students aged 8-11 years. The purpose of determining age criteria is to adapt to Jean Piaget's cognitive development theory (for the pre-operational stage and the concrete operational stage) and Jerome S. Bruner's learning theory (for the iconic stage and the symbolic stage). Data collection techniques using test techniques and data analysis used using the Kendall level correlation method Based on the results of the Kendall level correlation test it is concluded that: first there is a correlation between Jean Piaget's theory of cognitive development (pre operational stage) and Jerome S. Bruner's learning theory (iconic stage) in learning related to the process of the occurrence of a rainbow with the degree of closeness of the relationship that occurs between the two is 0.733 or 73.30%; secondly, there is a correlation between Jean Piaget's theory of cognitive development (concrete operational stage) and Jerome S. Bruner's learning theory (symbolic stage) in learning related to the process of the occurrence of rainbows with the degree of closeness of the relationship that occurs between the two of them is 0.867 or 86.70%.